Presentation of undiagnosed mixed mitral valve disease during caesarean section - Michelle R. Cole (Wolters Kluwer Medknow Publications, 2014)
This report describes a woman presenting for an elective caesarean section, with undiagnosed valvular heart disease. She had recent hospital admissions for respiratory dysfunction. Soon after the initial surgical incision, she became asystolic for 20-30 s with an un-recordable blood pressure. She was treated with anticholinergics and became cardiovascularly stable enough for the procedure to continue. However, she had deteriorating respiratory function. A transthoracic echocardiogram in recovery demonstrated mixed mitral valve (MV) disease, moderate mitral stenosis, and severe mitral regurgitation with evidence of severe pulmonary hypertension. She had a dilated left atrium, dilated right ventricle with pulmonary artery systolic pressures of 100 mmHg. She underwent a period of medical optimization followed by a mechanical MV replacement 6 weeks postdelivery. This case attempts to highlight the diagnostic dilemma of unknown maternal cardiac disease. The growing popularity of echocardiography as a diagnostic tool among anaesthetists and critical care physicians proved pivotal in this case.